2016
DOI: 10.3835/plantgenome2016.06.0051
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Association Mapping Reveals Novel QTL for Seedling Leaf Rust Resistance in a Worldwide Collection of Winter Wheat

Abstract: Leaf rust of wheat (Triticum aestivum L.) is a major disease that causes significant yield losses worldwide. The short-lived nature of leaf rust resistance (Lr) genes necessitates a continuous search for novel sources of resistance. We performed a genome-wide association study (GWAS) on a panel of 1596 wheat accessions. The panel was evaluated for leaf rust reaction by testing with a bulk of Puccinia triticina Eriks. (Pt) isolates collected from multiple fields of Oklahoma in 2013 and two predominant races in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 89 publications
2
47
1
Order By: Relevance
“…Chromosome 4A appears to be an important genome region with a high potential for leaf rust resistance in wheat. Correspondingly, promising loci were previously detected in association studies observing adult plant resistance in a set of American spring wheat (Gao et al 2016) and in a diverse core set including winter and spring wheat (Li et al 2016) or considering seedling resistance in a wheat collection of CIMMYT (Juliana et al 2018). The detected single nucleotide polymorphism (SNP) BobWhite_c47168_289 (SNP332) was also found as significantly associated with leaf rust resistance on wheat chromosome 4A by Gao et al (2016).…”
Section: Specific Hybrid Combinations Outperformed Parental Lines Formentioning
confidence: 86%
“…Chromosome 4A appears to be an important genome region with a high potential for leaf rust resistance in wheat. Correspondingly, promising loci were previously detected in association studies observing adult plant resistance in a set of American spring wheat (Gao et al 2016) and in a diverse core set including winter and spring wheat (Li et al 2016) or considering seedling resistance in a wheat collection of CIMMYT (Juliana et al 2018). The detected single nucleotide polymorphism (SNP) BobWhite_c47168_289 (SNP332) was also found as significantly associated with leaf rust resistance on wheat chromosome 4A by Gao et al (2016).…”
Section: Specific Hybrid Combinations Outperformed Parental Lines Formentioning
confidence: 86%
“…Genome‐wide association studies have been reported as being a useful approach to identify linked markers with genes controlling important agronomic traits (Zhu et al ., ). In recent GWAS, using DArT and SNP (single nucleotide polymorphism) markers, several genetic regions associated with resistance to leaf rust in wheat have been identified (Crossa et al ., ; Kertho et al ., ; Gao et al ., ; Jighly et al ., ; Li et al ., ). In the present study, 13 QTLs associated with resistance to leaf rust were found linked to 14 DArT markers on the chromosomes 1BL, 1DS, 2AS, 2BL, 2DS, 3BS, 3BL, 4AL, 6BS (two), 7DS, 5BL/7BS and 6AL/6BS.…”
Section: Discussionmentioning
confidence: 97%
“…Resistance to fungal diseases, and particularly to P. triticina , constitutes a valuable target trait for conducting genome‐wide association studies (GWAS). Recent studies using this methodology have identified several quantitative trait loci (QTLs) for resistance to leaf rust (Crossa et al ., ; Kertho et al ., ; Gao et al ., ; Jighly et al ., ; Li et al ., ). As the variation of complex traits usually shows QTL × environment interaction (QEI) (Mathews et al ., ), this should be considered to determine whether the genetic factors are reasonably stable across environments, determining their potential value in breeding programmes.…”
Section: Introductionmentioning
confidence: 97%
“…In addition to QTL analysis, which is based on phenotypic and genotypic polymorphisms within a bi-parental mapping population, association mapping is also applicable to a much larger gene pool and a more diverse genetic structure (Remington et al, 2001). Whole-genome association mapping has been applied to common wheat for several agronomic traits (Breseghello and Sorrells, 2006;Crossa et al, 2007;Neumann et al, 2011;Le Gouis et al, 2012;Edae et al, 2014;Wang et al, 2014;Zanke et al, 2014Zanke et al, , 2015Zanke et al, , 2017Li et al, 2016). However, these studies focused on a common wheat (T. aestivum) population but not on other hexaploid Triticum species.…”
Section: Introductionmentioning
confidence: 99%